Prediction of the force?drift envelope for RC columns in flexure by the CAE method. - Peru?, Iztok (Earthquake engineering & structural dynamics.)
A non-parametric empirical approach, called the conditional average estimator (CAE) method, has been applied for the prediction of the normalized lateral force?drift envelope of reinforced concrete (RC) rectangular columns, as well as their characteristic drifts (effective yield drift, capping drift and ultimate drift), and drift-related parameters (the ratio between the effective yield drift and elastic drift, and two ductility measures). A subset of the PEER RC column database was used. Five input parameters were employed: axial load index, index related to confinement, shear span index, concrete compressive strength, and longitudinal reinforcement index. The results suggest that the relations between the input and output parameters are complex, and that it is difficult to isolate the influence of a single parameter. Nevertheless, some trends were observed. The axial load index is the most influential input parameter. All the results decrease with an increasing axial load index, whereas they increase with an increasing longitudinal reinforcement index. An increase in the index related to confinement results in increases in the ultimate drift and in ductility. The influence of the shear span index is the most complex. The influence of the concrete strength is small with the exception of two output parameters related to elastic drift, which substantially decrease with increasing strength. The dispersion of the results is relatively large. The results of the predictions can be used for mathematical modelling of moment?rotation backbone curves for plastic hinges, and for the estimation of the deformation capacity of columns in seismic performance assessments.